2013
DOI: 10.18697/ajfand.56.12580
|View full text |Cite
|
Sign up to set email alerts
|

Geophagia clay soil as a source of mineral nutrients and toxicants

Abstract: Geophagia, which involves ingestion of non-food lithospheric substances, is the major form of pica in many African cultures. A common lithospheric pica substance ingested in the Cape Three Point region of West Africa, particularly Ghana and Togo, is a white loamy clay soil. This clay soil is usually ingested by women of reproductive age. Some of the reasons assigned to clay geophagia include appealing flavour, to alleviate nausea during pregnancy, and for absorption of toxins in the gastrointestinal tract. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 31 publications
4
19
4
Order By: Relevance
“…From our results, the levels of Arsenic obtained was below the mean exposure level of 3.0 µg/Kg BW/day set by the Joint FAO/WHO Expert Committee on Food Additives [31]. Tayie et al [10] reported 0.0 (nil) mg/Kg of Arsenic in clay samples in Accra were found to be lower than results obtained in this study. However, Nkansah et al [27] reported a range of 218-271 ppm from clay samples obtained from different parts of Kumasi Metropolis.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…From our results, the levels of Arsenic obtained was below the mean exposure level of 3.0 µg/Kg BW/day set by the Joint FAO/WHO Expert Committee on Food Additives [31]. Tayie et al [10] reported 0.0 (nil) mg/Kg of Arsenic in clay samples in Accra were found to be lower than results obtained in this study. However, Nkansah et al [27] reported a range of 218-271 ppm from clay samples obtained from different parts of Kumasi Metropolis.…”
Section: Discussioncontrasting
confidence: 90%
“…Lead concentrations were observed to be below the mean exposure levels and was in contrast with findings of range of values 549-622.92 µg/Kg reported by Nkansah et al [27]. In line with our results, Tayie et al [10] reported 2.36 ± 0.08 mg/100g. Lead consumption can result in adverse health effects such as the dysfunction of some vital organs such as kidneys, liver and heart.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, agricultural productivity has not reached its potential so far and people living in the area who depend on staple foods from their agriculture have paradoxically witnessed micronutrient defi-ciencies (a hidden hunger) due to the lack of nutrient dense quality foods (Melaku Umeta, 2003). (Mclean and Langille, 1976;Brennan et al, 1993;Srivastava et al, 1996;Shituu, 2013;Tayie et al, 2013). Distilled de-ionized water was used throughout the analysis.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Table 3 shows the Permitted Daily Intake (PMTDI) of the heavy metals. To evaluate the risk of heavy metals from clay consumption at the extreme, we made the following assumptions in this research: the ingested dose was equal to the absorbed pollutant dose [25]; cooking (baking) has no effect on the pollutants [26]; the average adult body weight of Ghanaians was 60 kg [27]; Average daily consumption of clay in Ghana is 70 g clay per day [10]. Therefore, the EDI of heavy metals for adults was calculated as follows: See formula 1 in the supplementary files.…”
Section: Tolerable Daily Intake and Estimated Daily Intakementioning
confidence: 99%